Influence of Middle East on pondok and madrasah education in the Malay Peninsula in the 19th and early 20th Century - Maarof, Nurul Hafizah; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
Islamic educational system in the Malay Peninsula began with the arrival of Islam to the region. The need for Islamic education by the natives of the Malay Peninsula grew exponentially from as early as the 18th to the early 20th centuries. As a result of the natives’ cumulative need, pondoks and madrasahs were formed as early as in the 19th and the early 20th centuries respectively. Both educational institutions were initiated by ‘ulama and Muslim modernists, who experienced the Makkan and Cairo educational systems. These educational institutions played an important role in educating the Malays since they provided the best education compared to vernacular and secular schools, which were established by the British. This book examines the role of ‘ulama and Muslim modernists in transforming the idea of traditional and modern religious system in the region from early 19th to the early 20th century. In addition, it also focuses on the features of both educational institutions and their impact on the native Malays in the region. In a nutshell, Malay Muslims’ education in the region particularly at the pondok and madrasah is a transformation of the Middle East Islamic educational system. This idea, which was initiated by u’lama and Muslim modernists, have brought many improvements towards the Malay society in areas of politics, social, and economic developments.